Analisis Kinerja Berdasarkan Rasio Likuiditas, Solvabilitas dan Rentabilitas pada Agroindutri Tahu Bulat Putra Mandiri di Dusun Buniasih, Desa Muktisari, Kecamatan Cipaku, Kabupaten Ciamis - Yaya Sunarya; Agus Hendar; Apdan Pebriana; Dudung Dudung; Riantin Hikmah Widi (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2025)
Agro-industry is a strategic sector that supports rural economic growth and food security. Agro-industry, as a strategic sector, often faces challenges in financial management, which have an impact on business stability and sustainability. This research analyzes the financial performance of the Tahu Bulat Putra Mandiri Agroindustry in Ciamis Regency based on liquidity, solvency and profitability ratios. Financial report data for the last three years (2022-2024) was analyzed using the case study method by calculating financial ratios, such as current ratio, quick ratio, debt to asset ratio, debt to equity ratio, return on assets (ROA), and return on equity (ROE). The results show fluctuations in financial performance, where the liquidity ratio is good enough to meet short-term obligations, but solvency reflects high financial risk due to dependence on debt, while profitability experiences a decrease in efficiency in generating profits. This research recommends improving capital structure, increasing operational efficiency, and business diversification to ensure the company's financial sustainability and stability.